International Conference on Radar Systems (Radar 2017) 2017
DOI: 10.1049/cp.2017.0401
|View full text |Cite
|
Sign up to set email alerts
|

Automatic vehicles classification approaches for WiFi-based Passive Forward Scatter Radar

Abstract: This paper shows the feasibility of a passive forward scatter radar (PFSR) based on WiFi transmissions for automatic classification of surface vehicles. To this purpose, proper automatic classification schemes are employed, able to exploit the forward scatter target signatures in the time domain. The considered approaches have been extensively tested against experimental data sets. The reported results prove that the exploited geometry yields quite stable and diverse signatures for the considered targets despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…The proposed approaches are extensively tested against experimental datasets in order to verify their practical feasibility. This paper is a companion to another paper submitted to this conference [1]. Specifically, with the proposed approaches we complement and extend the results in [1] by providing an effective solution for a realistic implementation of the conceived sensor.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…The proposed approaches are extensively tested against experimental datasets in order to verify their practical feasibility. This paper is a companion to another paper submitted to this conference [1]. Specifically, with the proposed approaches we complement and extend the results in [1] by providing an effective solution for a realistic implementation of the conceived sensor.…”
mentioning
confidence: 57%
“…In a companion paper submitted to this conference [1], we have shown that a WiFi-based passive radar system can be successfully exploited for surface vehicles automatic classification by adopting a forward scatter radar geometry, i.e. an extreme bistatic configuration where the bistatic angle is close to 180°.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNR=30 dB. The curves are scaled to the expected background level for each case, evaluated using (21), so that the result is representative of the expected signal-to-disturbance ratio. Apparently, progressively smaller values of 𝜂 have to be preferred as the target moves far from the baseline.…”
Section: Integrated Sub-bands Processing Schemementioning
confidence: 99%
“…The studies reported in the open literature addressing passive forward scatter radar (PFSR) have investigated the above aspects when parasitically exploiting different illuminators of opportunity operating from Very High Frequency (VHF) to K bands [11], there including Global Navigation Satellite System (GNSS) transmitters [9][10] [13][17] [18], Global System for Mobile Communications (GSM) and Long-Term Evolution (LTE) base stations [12] [20], radio and television broadcast transmitters [14][15] [22], and WiFi access points [16] [19] [21]. Many of these studies focused on the capability of a PFSR to detect and track ground-based or aerial targets, whereas some of them have investigated the potential for improved automatic target classification [18]- [21].…”
Section: Introductionmentioning
confidence: 99%